GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 1109319338 species occurrences available in GBIF matching the query: HasCoordinate: true Year: 1970-2019 HasGeospatialIssue: false. The dataset includes 1109319338 records from 17437 constituent datasets: 1 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 550 records from Pollen and spore abundance of Hole 42-380A. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 9998 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 7 records from Analyses of the recent components of sediment core PS1277-1. 352 records from Nannofossil abundance of Hole 60-458. 3374 records from MEXU/Leguminosae. 18 records from Nannofossil abundance of Hole 29-283A. 6368 records from DBRC Arvicola amphibius records 1925 - 2016. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 2781 records from Spider Mites Collection of Jean Gutierrez. 26 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 26 records from Schulteich Heinrich-Mann-Schule. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 570 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 6192 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1960 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 717 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 19 records from Coccolith counts of multinet M32/5_MSN988. 146673 records from R. L. McGregor Herbarium Vascular Plants Collection. 1191 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 20383 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 3 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 2130 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 389 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 18 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 82 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 154 records from Sorensen distance for herbivores. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1195063 records from First Bird Atlas. 661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 8648 records from University of Ghana - Ghana Herbarium. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 7422 records from Inventario de Hymenóptera; parasítica en México. 19066 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1798 records from 3Soil16S. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 68 records from Nannofossil abundance of Hole 24-233A. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 55 records from Dinoflagellate abundance of Hole 28-274. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 5 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 26221 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 68 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 21888 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 616 records from Whale catches in the Southern Ocean. 357 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 31014 records from River Biologists' Database (EPA). 49805 records from CABI Africa Invasive and Alien Species data. 7469 records from Eurobodalla Regional Botanic Gardens. 55 records from Great Eastern Ranges - Slopes to Summit. 50 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 97731 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8847 records from Odonata records from RSPB Reserves 1970-2009. 1031 records from Données supplémentaires Atlas des Mammifères marins. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 34332 records from Protist Diversity in the East China Sea. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1670677 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 275 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 22 records from Ostracoda abundance of Hole 24-238. 21 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 388 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 2670 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8803 records from NE Scotland other invertebrate records 1800-2010. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6279 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 558 records from Foraminifera abundance of Hole 74-526A. 267 records from Dinoflagellate abundance of Hole 81-555. 46 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1694 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 8909 records from EDIT - ATBI in Gemer area (Slovakia). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 21734 records from Global compendium of Aedes albopictus occurrence. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 186 records from Nannofossil abundance of Hole 27-259. 15073 records from UTEP Vertebrates. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 150 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 3973 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 6302 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 2300 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 31152 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 30 records from Nannofossil abundance in sediment core PS1313-4. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 399 records from Planktic foraminifera abundance of Hole 14-142. 39308 records from Insects, Outer Hebrides. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 7446 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 9990 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1739 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 124 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 16739 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 4880 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 88 records from Total foraminifera counts from M35/1_MSN1065. 2526 records from Marine Turtles. 196 records from Foraminifera abundance of Hole 33-317A. 574 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 4230 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 1624 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 67669 records from Données de l'Observatoire de la Faune de Bourgogne. 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 1208 records from Microbial diversity studies of Arabian Sea sediment. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 183 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 220 records from Echinoderms from the Seaflower Biosphere Reserve. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 218 records from Nannofossil abundance of Hole 49-408. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 11 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 98354 records from Allan Herbarium (CHR). 38811 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 13936 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 21 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 6 records from Foraminifera abundance of Hole 58-442. 7264 records from Uncultured eukaryotes Targeted Locus (Loci). 253 records from Données naturalistes d'Olivier LAURENT. 22728 records from Restauración y conservación de Isla Guadalupe. 4190 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 211 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 36 records from Planktic foraminifera counts of sediment core V28-122. 14 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 473 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 14766 records from University of Guam Insect Collection. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 126 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 90 records from Invasive species - Rosse stekelstaart (Oxyura jamaicensis) in Flanders, Belgium. 5068 records from National Botanic Garden Belgium - Myxomycetes. 150 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 5 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2415 records from Amphibian and reptile data for Dumfries and Galloway.. 515 records from Museu de Ciències Naturals de Barcelona: BGJBB. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 216 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 21 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 11364 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 45 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 25216 records from OPIE_National_2017_12_18. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 825 records from UWIZM Molluscs. 14331 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 122540 records from CAS Herpetology (HERP). 2 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 224 records from (Table 2g) Nannofossil distribution chart of petroleum well Swan-3. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 3667 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 107 records from orthopteracollections-nhmj-ioj. 639 records from Bird specimens of Saitama Museum of Natural History. 178 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 889 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 788 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 560121055 records from EOD - eBird Observation Dataset. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 383 records from Mycology collection, Norwegian Forest and Landscape Institute. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 58161 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification certaine. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from Dinoflagellate abundance of Hole 14-144. 6 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 12 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 6841 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 171 records from Total foraminifera counts of multinet M21/6_MSN787. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 12604 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 30 records from UWIZM Anoles. 138 records from West African pholcid spiders: an overview, with desriptions of five new species (Araneae, Pholcidae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 3 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1064 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 286 records from Odonata del Museo de Entomología de la Universidad del Valle. 1478 records from Geochemistry and sedimentology on core POS200/10_6-2. 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 11369 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 434986 records from Vascular Plants, Field notes, Oslo (O). 3 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 1 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 3442 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 46 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 4 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 26 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 283 records from An updated checklist of aquatic plants of Myanmar and Thailand. 2 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1702 records from BioGIS - Bryophytes - HUJ collections. 741 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 3362 records from (Table 7) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-873B. 23 records from Données naturalistes d'Océane ROQUINARC'H. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 843 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 5 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 1262 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 64 records from Pilzlehrwald. 2421061 records from International Barcode of Life project (iBOL). 1 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 601 records from LBV 100 - Artenvielfalt am Rothsee. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 115 records from Données naturalistes de Xavier BONNET. 117 records from Abundance of radiolaria at station UT99-5-1. 49 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 20814 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 329791 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 3119 records from Plecoptera. 3 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 44 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 2 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 20745 records from Mesures compensatoires A65 (CDC Biodivsersité). 114 records from Flora. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 98 records from Foraminifera species abundances from tow TT011_5-MOC63. 84 records from BIRDRACE Avinauten. 148 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 7 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 14 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 3422 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 1665 records from Collection Mollusca SMF. 73826 records from Lichen field notes, Oslo (O). 1410 records from Flore des Pyrénées. 61748 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 167 records from Total foraminifera counts of multinet M6/7_MSN100. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 54 records from Total foraminifera counts of multinet M21/4_MSN707. 6705 records from Données naturalistes de Benoit MARTHA. 15 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 344 records from Foraminifera abundance of Hole 22-215. 75451 records from Observations occasionnelles Parc national des Pyrénées. 383 records from Neogene palynomorpha from site 81-552. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 1268 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 51 records from Records of the Victorian Conservation Seedbank. 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 123 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 14294 records from Bird survey of Budai salt pans in Taiwan. 26280 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3003 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 176 records from Microfossil abundance of Hole 18-173. 10 records from Oberservation of birds at station PS14/143 along 49° West. 47752 records from The digitization of plant specimens of NTU. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 851 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 2560 records from Upper Silesian Museum, Bird Observations. 113 records from Planktic foraminifera abundance of Hole 26-250. 515 records from DREAL Auvergne - Amphibiens - 2015. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 554 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 1602 records from Données naturalistes de Quentin ROME. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 11399 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 116 records from SEWBReC Springtails and allies (South East Wales). 849277 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 554 records from Percentages of planktonic foraminifera species in sediment core V29-144. 84210 records from The Himalayan Uplands Plant database (HUP Version 1). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 5 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 131 records from Artenvielfalt auf dem Schulgelände. 1713 records from Données Circus maillardi du Parc national de La Réunion - COBE02. 6958 records from Siliceous microfossil occurrence, Site 177-1091. 4982 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 330 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 597 records from Range table from benthic foraminifers in ODP Hole 149-900A. 117 records from Streuobstwiese Stedar 2009. 149 records from Total foraminifera counts of multinet M21/2_MSN640. 58 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 735 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 445 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 1326 records from Sistematización de la colección de peces del centro de México. 98 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 91 records from Diatom abundance of Hole 95-613. 38 records from UCLA Donald R. Dickey Bird and Mammal Collection. 8 records from Die Bachspezies 2008/2009. 1536 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 61 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 45117 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 1 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 68 records from Streuobstwiese. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 396 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 15 records from Description of lithologic section units of IODP Hole 325-M0041A. 10551 records from Données RNR Vacherie. 19 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 4209 records from Plant specimens of Obihiro Centennial City Museum. 389151 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 84 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 3965 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 4510 records from Carabidae of the Carpathians. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 418 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2250548 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 452 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 57 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 74481 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 260081 records from ARABEL - Arachnologia Belgica. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 15136 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 33209 records from Wolli Creek Preservation Society Bird Survey. 553 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 469 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 29 records from UWYMV Herpetology Collection (Arctos). 11873 records from Midden-Limburg Fish Ponds Survey. 32567 records from Herbarium Senckenbergianum (FR) - Fungi. 1985 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 240 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 158 records from Planktic foraminifera counts at CTD station PS55/063. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 3975 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 13 records from Benthic macrofauna abundance of sediment core 12930-063. 335 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 11267 records from INNS Data: All Taxa (West Wales). 148 records from Überall ist Wunderland. 2451 records from Macrobenthos Chukchi Sea, 1986. 1561 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 208 records from Condamine Alliance. 1 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 16 records from Microzooplankton abundance and biomass at station TT043_13-1. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 8 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 2 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 485 records from Données naturalistes de Marie-France LECCIA. 481 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 168 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 107 records from Faunal assemblage of sediment core TR149-31. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 17364 records from Microbial community in marine sediments. 152 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 2059 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 54 records from Nannofossil abundance of Hole 49-409. 13701 records from Herbier Louis-Marie (QFA) - Collection de lichens. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 16 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 164952 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 1709 records from suspended particulate matter Raw sequence reads. 374 records from USGS Alaska Science Center Polar Bear Maternal Dens. 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 18392 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 249 records from Calcareous dinoflagellates nominated in grain fraction > 20 µm. 190 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 1997 records from Aves de la cuenca media del río Bogotá. 5244 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 4319722 records from Observations du Conservatoire botanique national du Bassin parisien.. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 6103 records from Colecção Entomológica IIA. 16612 records from MZFC/Coleccion de Aves. 352 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1273 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 164 records from Foraminifera abundance of Hole 48-406. 1040815 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 61 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 130230 records from Macaulay Library Audio and Video Collection. 623 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 2157 records from Museu Darder de Banyoles. 521 records from Benthic foraminifera abundance of Hole 82-558. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 316 records from Moss species from Heard Island, 1987 and 2000. 52 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 1 records from DMNS Egg Collection (Arctos). 930 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 6 records from Wuhle - Brücke / B1. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 3474 records from Marie-Victorin Herbarium (MT) - Bryophytes. 462 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 315 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 8332 records from Scotland Otter Survey Database. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 994 records from Utah State University, Intermountain Herbarium. 204745 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 908 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 904 records from Nannofossil abundance of Hole 15-149. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1868 records from Registros Primates Neotropicales Convocatoria APC. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 12 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 5791 records from La familia Asclepiadaceae en México. 2 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 311 records from Benthic foraminifera abundance of Hole 41-366A. 370 records from Otter survey of Ireland 2004 & 2005. 1052 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 9968 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 23 records from Landwehrbach. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 931 records from Microfossil abundance of Hole 16-158. 406 records from Nannofossil abundance of Hole 78-543. 5758 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 6865 records from University Of Pretoria: Lacewing Database Project (1911-2015). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 2782 records from USAC Mammals Collection. 195 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 121 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3106 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 37 records from Planktic foraminifera counts of sediment core RC13-154. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3320 records from BioGIS - Mammals - SPNI. 19 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 909975 records from SEWBReC Birds (South East Wales). 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 231 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 782 records from Planktic foraminifera abundance of Hole 42-372. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 17291 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1590 records from MEXU/Flora de Oaxaca. 5847 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9743 records from marine sediment metagenome Raw sequence reads. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 131978 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 6999 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 1698 records from Red-throated diver national surveys in Scotland - raw data. 215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14805 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 530728 records from Données de la flore d’Alsace (SBA). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4968 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 110 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 936 records from Distribution of benthic foraminifera on sediment core sediment core PS1290-4. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 95 records from Abundance of radiolaria at station UT99-19-2. 34 records from Nannofossil abundance of Hole 20-199. 64 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 489 records from Royal BC Museum - Herpetology Collection. 3 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 7773 records from National Museum of Natural Science. 85 records from Total foraminifera counts from M35/1_MSN1043. 127 records from Planktic foraminifera abundance of Hole 14-140. 234 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 111 records from Global Ocean Sampling Expedition. 143 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1497 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 1030 records from New Brunswick Museum Collection. 61 records from Range table from benthic foraminifers in ODP Hole 144-874A. 13 records from Collections ichtyologiques et herpétologiques (BOUM). 26 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 14971 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3154 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 54 records from Données "faune" de LABBAYE Olivier pour le SINP île de France. 139 records from Abundance of radiolaria at station LV28-40-2. 63053 records from Norwegian Lepidoptera working group. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 5 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 5373 records from Lichens of North-Eastern Poland. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 2 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6172 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 41 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 6 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 648 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 6 records from Coccoliths in sediment core PS1532-9. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 95 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Sächsische Schweiz (Pfaffenstein). 11944 records from Données ONEMA BDMAP 2014. 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 4298 records from ColRest_Raw1. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 4610 records from Wetland Algae. 5991 records from SNH Bat Casework records 1970-2007. 5 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 187 records from Phytoplankton abundance at station CD46_1305C#2. 2354 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 125 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 12 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 501 records from Planktic foraminifera abundance of Hole 74-525B. 905 records from Naturhistorisches Museum Mainz, Botanical Collection. 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 7609 records from Amundsen Gulf Overwintering Eukaryote Community. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 84 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 4 records from Microplankton abundance at bottle station SEPT-1999-K2. 3755 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 2 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 10363 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 14 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 816 records from IRAD Cameroon insect collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 9146 records from Grand_Site_Sainte-Victoire_2017_12_18. 266 records from Ostracoda abundance of Hole 95-612. 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 107 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 9 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 4 records from Planktic foraminifera abundance of Hole 19-191A. 14232 records from AMNH Bird Collection. 22052 records from CNIN/Abejas de México/Apoidea. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1262 records from Flora útil del Municipio de la Huerta, Jalisco. 3575 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 828 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 2134 records from Kurzflügler_Raw1. 880 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1168 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 2 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 15 records from Nannofossil abundance of Hole 10-93. 2189 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 12665 records from RECORD Bryopsida Data. 7 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 12 records from Art´n Vielfalt im Kinderwald. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 3724 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 385 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 4 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 1110 records from FFH-Gebiet "Calwer Heckengäu". 211 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 195 records from Naturalis Biodiversity Center (NL) - Crustacea. 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 2127 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 1 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 1 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 81532 records from Bob Merritt Coleoptera Dataset. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 101 records from Component analysis of TV-guided grab sampler GeoB10071-5. 4 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 436 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 14736 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 1074 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1282926 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 43 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 411861 records from DATAVES. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 105 records from Projet Diable de mer - AILERONS. 297 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 5 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 885 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 27 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 433 records from The Broward College Insect Collection. 135 records from Planktic foraminifera abundance of Hole 73-524. 62 records from Total foraminifera counts of multinet M10/2_MSN229. 7 records from Planktic foraminifera abundance of Hole 53-418B. 2 records from Données naturalistes de LEMOIGNE JONATHAN. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 16 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 424 records from Distribution of nanoplankton at trap WR2. 103 records from Schwanseepark (87645 Schwangau). 13624 records from Ecosphère_2017_12_18. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 114 records from BIRDRACE VIE will rock you!. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 522 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 70067 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 793 records from Isle of Wight non-native invasive species. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 1 records from Synthèse de la répartition des populations de cerf élaphe en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 581 records from Floristic records in the Moscow and Novgorod regions. 15397 records from Macrophyte Lake Data. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 117904 records from Biological Impacts of Ocean Acidification. 182 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1335 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 14894 records from Colección Ictiológica del Instituto Alexander von Humboldt. 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 3 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 210 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 819 records from Coléoptères Silphidés du département du Loiret. 1168 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 122 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1924 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 97031 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 14235 records from EAC - Herbário Prisco Bezerra. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 1509 records from Collection Crustacea - ZMB. 612 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 500 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 36 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 414 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 32660 records from The national database for marine data (MADS). 31 records from Nannofossil abundance of Hole 9-82. 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 153 records from Planktic foraminifera abundance of Hole 18-181. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 4513 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 337 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 283 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24443 records from Plan de vertebrados de la Patagonia. 2400 records from Springtales from lichen communities at Kollåsen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 268 records from Planktic foraminifera abundance of Hole 22-217. 304444 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 975 records from Danielsberg (Mölltal, Kärnten). 73 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 8 records from Nannofossil abundance of Hole 39-353A. 16985 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 191 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1953 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6570 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 41130 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 186 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 5212 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 895 records from MEXU/Tipos de plantas vasculares. 15 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 8 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 165 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 30 records from Averages and ranges of paleoenvironmental proxy records of ODP Hole 108-658C (Table 1). 128 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 57 records from CSIRO Yellow Box Fragmentation Project. 209 records from Nannofossil abundance of Hole 94-610B. 673 records from Planktic foraminifera abundance of Hole 45-395. 18937 records from Entomology Collection at the Natural History Museum of Utah. 20044 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 98 records from Total foraminifera counts of multinet M21/2_MSN644. 4 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 76785 records from ALCB - Herbário Alexandre Leal Costa. 138 records from (Table 7) Dinoflagellate cyst species distribution in ODP Hole 112-680B. 114 records from BIRDRACE LiLaLau. 3693 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 46186 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 1 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 87 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 2064 records from UTEP Invertebrates (Arctos). 6 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 26614 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 216664 records from Carnet B Lorraine. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 475 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 550 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 291 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 38 records from Planktic foraminifera abundance of Hole 84-566C. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 847 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 128 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 43027 records from Arizona State University Hasbrouck Insect Collection. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 18 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 35 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 108 records from Nannofossil abundance of Hole 31-299. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 45 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 99 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 277 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1186 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 853 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 67938 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1036 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 346 records from Birds and plant species near Petushki town (Vladimir region). 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 53788 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 40 records from Planktic foraminifera abundance of Hole 14-137. 500 records from UWYMV Bird Collection (Arctos). 1574417 records from Hatikka Observation Database. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 109853 records from inatura - Erlebnis Naturschau Dornbirn. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 386 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 3792 records from Sea water microorganisms Raw sequence reads. 1136059 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1500 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 2317 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 45 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 22406 records from WTSWW Data: All Taxa (West Wales). 172 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412316 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 211598 records from South Australian Museum Australia provider for OZCAM. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 52 records from Brock University Herbarium (BU). 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 75 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 60 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 128179 records from Tasmanian Museum and Art Gallery provider for OZCAM. 403 records from TTRS Mammals. 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 2 records from Benthic foraminifera abundance of Hole 42-376. 355 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 92185 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 9 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 128 records from Faunal assemblage of sediment core TR149-32. 84 records from Total foraminifera counts from M35/1_MSN1051. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 794 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 209746 records from Estonian Nature Observations Database. 32090 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 7844 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 19 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 2612 records from Fungi specimens of Saitama Museum of Natural History. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 876 records from Bosque Mesófilo de Montaña de México. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 23181 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Collection ornithologique A. Maës. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 32 records from Mammal specimens of Komatsu City Museum. 12 records from Urban Barcode Project - Fungi. 270 records from ACT and Southern Tablelands Weed Spotter. 41 records from Örtzemündung (Stedden). 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 30233 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2860040 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 100 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 692 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 2486 records from NIWA Invertebrate Type Collection. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 5748 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 220 records from Malawi-Histeridae-Biodiversity-Data. 728 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 10987 records from Collections of Phytoplankton at BGBM. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 2990 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 58 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 3946 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3567 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 750 records from Carabidae of the European North-East of Russia. 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 1 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 17263 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2692290 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 224 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 473901 records from BioFokus. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15278 records from Anymals+plants - Citizen Science Data. 1288 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3383 records from Planktic foraminifera abundance of Hole 23-219. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 660 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 39 records from Planktic foraminifera abundance of Hole 27-260. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3576 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1369 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 62433 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2507 records from East Ayrshire Species Database. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 35 records from Nannofossil abundance in sediment core PS1293-4. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 3 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 7 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 116 records from Nannofossil abundance of Hole 20-200. 243 records from Thistles species and abundance. 60 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 102 records from A Lichen Survey of the Ben Nevis Plateau. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 14 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 519 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 310 records from Données naturalistes de Laurent PONCET. 19 records from Coccolith counts of multinet SO119_MSN1301. 2300 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 28590 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 142 records from Planktic foraminifera abundance of Hole 32-313. 1356 records from Royal Ontario Museum Fungarium (TRTC). 159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 45422 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 4686 records from Butterfly_conservation_2017_12_18. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 117060 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 34119 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 8 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 471 records from Benthic foraminifera counts of sediment core GIK23342-6. 99 records from Düne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 3 records from Données naturalistes d'Emilie WEBER. 17939 records from Mammals housed at MHNG, Geneva. 2 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 345 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 1831 records from Swiss Psyllid (Hemiptera) Collections - Basel. 10 records from Sediment properties of core PLG95B_01BOXG. 15 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 537 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 1059 records from Planktic foraminifera abundance of Hole 15-148. 258 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 133 records from UWIZM Mantodea. 472 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 4 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 17 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 579 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 3528 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 71 records from UNM Earth Sciences Collection (Arctos). 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10293 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 22 records from New records of ant species from Yunnan, China. 25 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 3388 records from Caracterización biológica en la Serranía de San Lucas 2015. 2394 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 281 records from Nannofossil abundance of Hole 22-217. 895 records from Bird specimens of Komatsu City Museum. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 135 records from Boreonemoral regnskog på østsiden av Lygrespollen. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 26 records from Liste des oiseaux de BZM Belambo. 140 records from Beetles on polypores at 4 sites in Norway. 72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 30 records from Collection Crustacea - ZSRO. 1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 1259 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 89 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 1 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 157 records from BIRDRACE Rheinische Wasserrallen. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 901 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1576 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 2747 records from Données naturalistes de David HAPPE. 1 records from A second contender for “world’s smallest fly” (Diptera: Phoridae). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 70919 records from Colección de Entomología del Instituto Alexander von Humboldt. 4 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 39504 records from Fife Nature Records Centre combined dataset. 52 records from CHAS Botany Collection (Arctos). 1441 records from Planktic foraminifera abundance of Hole 18-173. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 279 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 3684 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 213 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 10139 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 93934 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14534 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16505 records from Database for alien invasive plants occurrences in Germany. 12 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 44 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1337 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 793 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 84 records from Benthic foraminifera abundance of Hole 84-566C. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 2380 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 50925 records from National Biodiversity Data Bank. Observation records, 1900-2014. 319 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 15 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 12394 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 92 records from Nottekanal, Klasse 7 - 10. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 311 records from Nannofossil abundance of Hole 37-333. 3957 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1782 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 2724 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 896303 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 2829 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 235302 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 21157 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 38 records from Was lebt in der Brutzwiese?. 59 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 96 records from Planktic foraminifera abundance of Hole 22-212. 28 records from Biodiversity Surveys, South-east Arnhem Land. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 32 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 222046 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 102 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 74 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 53 records from Coleção de Nematoda do Museu Nacional - UFRJ. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 3 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 2536 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 5 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 1988 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 107 records from Total foraminifera counts from multinet M31/2_MSN890. 3 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 422 records from Collembola of the Chernaya river basin. 45 records from Estimated plankton abundance at station PS63/064-6. 932 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 16934 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 497 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 527 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 36280 records from EDP Foz Tua: Bat Roosts - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 1749 records from Benthic foraminifera abundance of Hole 84-570. 1090 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 2070 records from Algae collection. 5044 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 1 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 1669 records from Données naturalistes de Jean-Paul LECHAPT. 55 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 68 records from Planktic foraminifera abundance of Hole 16-161. 4104 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 6 records from Guinea-Bissau Herpetological Collection - IICT. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 908 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 5 records from Planktic foraminifera abundance of Hole 19-184B. 10771 records from Camera trapping bird data. 37 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 506 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2044 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 3287 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 266 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 364 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 221 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 20161 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 330 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 15 records from Benthic macrofauna abundance of sediment core 13200-047. 9 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 27 records from synthese_Protistdiversity_KG. 6279 records from SPC CoFish Fish Observations Palau 2007. 73496 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 76 records from Caracterización Floristica del Páramo Tatamá. 101 records from Planktic foraminifera abundance of Hole 28-265. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 101 records from Benthic foraminifera abundance of Hole 42-372. 1258 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 469144 records from Natural England Marine Monitoring surveys. 756 records from Range table from benthic foraminifers in ODP Hole 139-857A. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 356 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 3 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 27 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 2 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 122 records from Foraminifera species abundances from tow TT011_10-MOC71. 521 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 1 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 2537 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 10345 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 4378 records from Environment Agency Eiseniella tetraedra Records (England). 103 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 9 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 181 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 964 records from Coleoptera Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 21647 records from National River Water Quality Network Database (Macro-invertebrates). 202 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 1136 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 1 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 13142 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 264 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 310 records from Manual para la identificación de lianas en el campo. 831 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 540999 records from Welsh Invertebrate Database (WID). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 14 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 2171 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 3815 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 36503 records from Abundances indices and biological traits of juvenile salmon sampled in the Scorff river (France). 2 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 5 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1169 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 638 records from Benthic foraminifera abundance of Hole 56-435. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 11000 records from Données naturalistes de Pierre FRAPA. 1035 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 83 records from Naturpark Kottenforst-Ville 16.6.09. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 749 records from Planktic foraminifera abundance of Hole 15-154A. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 658 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 244 records from WildesMoor bei Schwabstedt. 336 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 150 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2179 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 128 records from Planktic foraminifera abundance of Hole 94-611. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 105 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 1995 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6581 records from Nijmegen Natural History Museum (NL) - Herbarium. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2499286 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 105 records from Total foraminifera counts of trap L2_92_A42. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 1170 records from Département_du_Var_2017_12_18. 127 records from Wildlife Observations Bardon Hill 31.5.09. 67 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 41526 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 3139 records from CTD water column metabarcoding. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 27 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 42 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 65 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 4 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 173497 records from Finnish Floristic Database (Literature Sources). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 2376 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 58022 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1766 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 7472763 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 276 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 175 records from Nannofossil abundance of Hole 41-366A. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 92 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 531 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 507 records from Planktic foraminifera abundance of Hole 84-567A. 136 records from Nannofossil abundance of Hole 39-359. 1857 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 152 records from Nannofossil abundance of Hole 49-412. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 26 records from Abundance of benthos infauna at station PS1240-1. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 29 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1260 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 19465 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 134 records from BIRDRACE Griffin Wood Warblers. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 915 records from Nannofossil abundance of Hole 30-286. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 4 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 59331 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 26820 records from University of Tennessee Bryophyte Herbarium. 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 41 records from Planktic foraminifera counts of sediment core V28-128. 3770 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 21712 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 6541 records from Likona Invertebrates. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 113 records from Collection Polychaeta - ZSRO. 14061 records from imr_mareano_rpsledge. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 55 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 3566 records from Gunma Museum of Natural History, Fungi Specimen. 313 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 2 records from Kirchenforst. 252 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 13110 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 3 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 9597 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 1755 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 35 records from Nannofossil abundance of Hole 15-146A. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 1424 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 295 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 152137 records from UWFC Ichthyology Collection. 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 58 records from Mamíferos laguna El Tinije. 23 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 16653 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 11044 records from Données naturalistes d'Anthony TURPAUD. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 512 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 22868 records from CUMV Fish Collection. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 2138 records from MUST, Insecta. 584050 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 32615 records from University of Tennessee Fungal Herbarium. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2165 records from University of Michigan Museum of Zoology, Division of Mollusks. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 2103 records from Flora ficológica de la huasteca potosina. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 319 records from Range table from benthic foraminifers in ODP Hole 144-874B. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 613 records from Données acquises via le réseau du CBNBP. 57608 records from DASSH Data Archive Centre Academic Surveys. 1344 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 78049 records from University of Florida Invertebrate Paleontology. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 695 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 608 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 43 records from Vogelstimmenführung durch den Tiergarten. 24437 records from Données naturalistes de Pierre JAY-ROBERT. 96 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 106 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 16738 records from Inventaire des Ephémères de métropole (Opie). 308 records from Echinodermata of Montenegro (South Adriatic). 9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 185 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 4498 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 6 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 47762 records from Atlas des Orthoptères et Mantides de France métropolitaine. 257 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 17267 records from UAM Bird Collection (Arctos). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 353106 records from Dry Tortugas Reef Visual Census 2014. 24 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 793 records from UTEP Herpetology Osteology (Arctos). 85137 records from The Scottish Squirrel Database. 96 records from BIRDRACE OAG Neuwerk. 203 records from Total foraminifera counts of multinet M21/1_MSN604. 15 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 32 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 270 records from BIRDRACE Niederlausitz-Team. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 4803 records from Odonata de Veracruz. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 2851 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2084 records from Flora vascular acuática de la cuenca del Río Tamesí. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 20 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 814 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 777 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 8675 records from Andes to Amazon Biodiversity Program. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 44 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 6 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 118 records from Natur aus zweiter Hand am Muldestausee. 176 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 253165 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 190 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 23 records from TBW-Schafberg. 4861 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 36 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 1 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 1686 records from HPL - Herbário do Jardim Botânico Plantarum. 1020 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 35 records from Benthic foraminifera abundance of Hole 42-381. 967263 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 36 records from Total foraminifera counts of multinet M42/3_MSN1368. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 2801 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 123527 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 313 records from Stadtpark Herzberg (Elster). 30 records from Nannofossil abundance of Hole 29-280. 131 records from Unser Schulhof - eine Apotheke. 691 records from Black grouse national surveys. 37 records from Berlin - Treptower Park / Karpfenteich. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 6972 records from El género Bursera en México. Parte II. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1309 records from Ocean crust Targeted Locus (Loci). 443 records from PSUZC-Mammal Collection. 1288 records from Canadian National Collection of Insects. 2 records from First description of the female of the spider Savignia zero Eskov, 1988 (Araneae: Linyphiidae). 425 records from GCP_2017_12_18. 361 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 8877 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1419 records from (Table 6) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1018A sediments. 87 records from Gulf of Gdansk. 11771 records from Museu Paraense Emílio Goeldi - Diptera Collection. 853 records from Planktic foraminifera abundance of Hole 80-549A. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 30 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-101BX. 1364 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 146 records from Benthic foraminifera abundance of Hole 34-320. 59 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 28675 records from Herbarium Senckenbergianum (FR). 167 records from Loup 2008 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 276 records from DREAL Auvergne - Reptiles - 2015. 8082 records from Invertebrate Zoology Division, Yale Peabody Museum. 19947 records from Merseyside BioBank Active Naturalists (unverified). 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 350 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 327 records from Ectomycorrhiza species on all VIP´s April 2008. 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 255 records from Planktic foraminifera counts of sediment core RC17-69. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 17 records from Nachtinsekten am Muldenufer. 59 records from Planktic foraminifera abundance of Hole 73-520. 621 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Ernst Krenkel" in 1992”. 2183 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 432847 records from Israel Nature and Parks Authority. 85 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 8 records from Sipuncula collection of National Museum of Nature and Science. 9303 records from Micro-moths distribution for Dumfries and Galloway. 1551 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 194 records from Pottundkopp. 488 records from Mamíferos: Colección Universidad de Caldas. 6654 records from Catálogo de insectos de la colección del Centro de Entomología. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 1185 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 324 records from (Table 3) Occurrence of dinoflagellate cyst species in ODP Hole 113-696B. 21 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 12 records from Nannofossil abundance of Hole 51-417B. 6 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 2 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1782 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 242 records from MPM Herpetology. 8 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 9240 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1475 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 2 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 2 records from The Vietnamese population of Megophrys kuatunensis (Amphibia: Megophryidae) represents a new species of Asian horned frog from Vietnam and southern China. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 1247 records from Antarctic Jellyfish. 41 records from Données naturalistes d'Audrey SAVOURE-SOUBELET. 357155 records from National Trust Species Records. 162441 records from Australian National Wildlife Collection provider for OZCAM. 6756 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 253 records from Pukkellaks i Norge 2017. 2748 records from HUSC - Herbário Unisanta. 10217 records from Crispin S. Guppy Collection. 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 63 records from Planktic foraminifera abundance of Hole 11-106B. 80 records from Données naturalistes d'Emmanuel ICARDO. 245 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1380 records from NHM, Heteroptera. 688 records from Algae, Norwegian College of Fishery Science. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 105 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1067 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 4 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 1 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 854492 records from Australian Museum provider for OZCAM. 1 records from 5. Wiener Gemeindebezirk. 26850616 records from Observation.org, Nature data from the Netherlands. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 97 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 8 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 7360 records from Mammal records for Dumfries and Galloway. 34 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 137 records from osac_oarisma. 88400 records from Vascular plant herbarium, Tromsø Museum. 70 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 183 records from Inventaire des Scléractiniaires de la région du Diahot. 36 records from Terre d'huiles. 91 records from BIRDRACE SchrägeVögel. 170509 records from England Non Native Species records 1965 to 2017. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 222 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 382 records from DBL_Life. 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 835 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 25011 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 1434 records from Nannofossil abundance of Hole 94-607. 2066 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new
Keywords: GBIF; biodiversity; species occurrences